cAMP-Dependent Signaling Pathways as Potential Targets for Inhibition of Plasmodium falciparum Blood Stages - Lasonder, Edwin; More, Kunal; Singh, Shailja; Haidar, Malak; Bertinetti, Daniela; Kennedy, Eileen J.; Herberg, Friedrich W.; Holder, Anthony A.; Langsley, Gordon; Chitnis, Chetan E. (Frontiers in Microbiology, 2021)
We review the role of signalling pathways in regulation of the key processes of merozoite egress and red blood cell invasion by Plasmodium falciparum and, in particular, the importance of the second messengers, cAMP and Ca2+, and cyclic nucleotide dependent kinases. cAMP-dependent protein kinase (PKA) is comprised of cAMP-binding regulatory, and catalytic subunits. The less well conserved cAMP-binding pockets should make cAMP analogues attractive drug leads, but this approach is compromised by the poor membrane permeability of cyclic nucleotides. We discuss how the conserved nature of ATP-binding pockets makes ATP analogues inherently prone to off-target effects and how ATP analogues and genetic manipulation can be useful research tools to examine this. We suggest that targeting PKA interaction partners as well as substrates, or developing inhibitors based on PKA interaction sites or phosphorylation sites in PKA substrates, may provide viable alternative approaches for the development of anti-malarial drugs. Proximity of PKA to a substrate is necessary for substrate phosphorylation, but the P. falciparum genome encodes few recognisable A-kinase anchor proteins (AKAPs), suggesting the importance of PKA-regulatory subunit myristylation and membrane association in determining substrate preference. We also discuss how Pf14-3-3 assembles a phosphorylation-dependent signalling complex that includes PKA and calcium dependent protein kinase 1 (CDPK1) and how this complex may be critical for merozoite invasion, and a target to block parasite growth. We compare altered phosphorylation levels in intracellular and egressed merozoites to identify potential PKA substrates. Finally, as host PKA may have a critical role in supporting intracellular parasite development, we discuss its role at other stages of the life cycle, as well as in other apicomplexan infections. Throughout our review we propose possible new directions for the therapeutic exploitation of cAMP-PKA-signalling in malaria and other diseases caused by apicomplexan parasites.